Perceived Risk Questionnaire in Canyoners: content validity, cross-validation and transcultural invariance across Portugal and Spain - António Brandão; Diogo Monteiro; Joel Pereira; Eduarda Coelho; Luís Quaresma (Desafio Singular, 2018)
The aim of this study was to develop and validate a questionnaire related to the risk perception in canyoning. Cross-validation and transcultural invariance, across Portugal and Spain, were also analysed. A total of 707 canyoners (81.3% males, 18.7% females) from Portugal (47.5%) and Spain (52.5%) participated in this study, with ages between 18 and 57 years old (M = 36.13; SD = 7.71). The initial version of questionnaire had 49 items. With the Temporal Reliability Analysis, the items that showed no correlation between the two moments of the administration of the questionnaire, p>.05, were removed and only 46 items remained. The Exploratory Factor Analysis was developed by choosing the 25 items with higher factorial weight. Six dimensions were found which we managed to identify and characterise with the help of literature. With the Confirmatory Factor Analysis and based on the analysis of the modification indices, 4 items were eliminated, as they presented very high residual values, which contributed to an inadequacy of the model. In this manner, a questionnaire with 21 items was achieved. The final version of the questionnaire showed acceptable values related to reliability and construct validation. Therefore, this allows it to be used in the risk perception in canyoning, with 21 items, distributed among 6 dimensions.